2022
DOI: 10.14254/2071-789x.2022/15-3/2
|View full text |Cite
|
Sign up to set email alerts
|

Migration and earnings in emigrant and immigrant countries - the case of Europe

Abstract: Migration flows within Europe intensified after the EU enlargement that enabled easier procedures for finding a job in another country. Among the various effects that migration can have on emigrant and immigrant economies, this paper aims to focus on and quantify the impact of migration flows on income levels in both groups of countries. The research covers the period of 2006-2019 and applies dynamic panel data analysis, the results of which highlight that the number of emigrants has a statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Yüksel et al, (2018) identified several fundamental push and pull factors which are economic, social, and political that may initiate the formation of individuals' emigration intentions. One key factor is income (Clemens, 2014;Kersan-Škabić & Blažević Burić, 2022) or perceived satisfaction with a household's financial conditions. The migration of skilled people is driven by the expected wage differential between the home and destination countries (Güngör & Tansel, 2008;Oliinyk et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yüksel et al, (2018) identified several fundamental push and pull factors which are economic, social, and political that may initiate the formation of individuals' emigration intentions. One key factor is income (Clemens, 2014;Kersan-Škabić & Blažević Burić, 2022) or perceived satisfaction with a household's financial conditions. The migration of skilled people is driven by the expected wage differential between the home and destination countries (Güngör & Tansel, 2008;Oliinyk et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rapid labour migration has become an extremely acute problem, especially in rural areas, it shapes the situation in regional labour markets, regulates the development of social and labour relations, employment, well-being, consumption, and processes of savings and reproduction (Chugaievska & Rusak, 2022). These differences can, however, be mitigated soon due to the migrants' impact on earnings in recipient countries (Kersan-Škabić et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%